Groundwater Hydrochemistry Evaluation using Graphical Tools - Shyamala G.; Jeyanthi J. (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Aim of the study was to investigate the groundwater resources at Coimbatore district. Contamination of ground water samples is analysed and compared with BIS Majority of the water samples are not suitable for domestic purpose and from drinking water standards however used for irrigation purpose .The study also reveal the groundwater at the area is dominated by parameters like calcium, magnesium and chloride. Continuous monitoring of groundwater is essential to conserve the natural groundwater quality.